Kardiochirurgia dorosłychOperative strategy enhancement following transit-time flow measurement in coronary artery bypass grafts - Maruszewski, Marcin; Borowicz, Marcin; Kubacki, Krzysztof; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Background: Patent bypass grafts are fundamental to successful coronary artery bypass grafting. Intraoperative flow measurement through newly constructed grafts is the best quality and patency test. The flow pattern in bypass grafts and its sensitivity to diagnose possible ischaemia, influence on perioperative strategy and early outcome were evaluated. Aim: Intraoperative flow measurement through newly constructed coronary grafts. Influence of perioperative strategy on early outcome in patients with perioperative ischaemia. Material and methods: From January 1 to August 20, 2003, 611 patients underwent isolated primary coronary bypass grafting in the Silesian Centre for Heart Diseases, Zabrze, Poland. 378 patients underwent conventional coronary artery bypass grafting and 233 underwent off-pump coronary artery bypass grafting. No perioperative flow measurements were carried out at that time. From August 21, 2003, to December 4, 2005, 2142 patients underwent isolated primary coronary bypass grafting. 1299 patients underwent conventional coronary artery bypass and 843 underwent off-pump coronary artery bypass grafting. 386 patients underwent intraoperative flow measurement (147 conventional and 239 off-pump). Graft patency was assessed using flow curves, mean flow, pulsatility index and diastolic flow value. Results: The rate of complications resulting from perioperative ischaemia (myocardial infarction, extended hospital stay, mortality, etc.) was lower after perioperative flow measurement was introduced as a standard of care. Conclusions: Introduction of intraoperative flow measurement has influenced the perioperative strategy. Validation of newly constructed graft by intraoperative flow measurement allows the rate of perioperative complications such as myocardial ischaemia and infarction to be minimized, both in conventional and especially off-pump coronary surgery.